Dynamics and Conformational Studies of TOAC Spin Labeled Analogues of Ctx(Ile21)-Ha Peptide from Hypsiboas albopunctatus - Vicente, Eduardo F. [UNESP]; Basso, Luis Guilherme M.; Cespedes, Graziely F. [UNESP]; Lorenzón, Esteban N. [UNESP]; Castro, Mariana S.; Mendes Giannini, Maria José Soares [UNESP]; Costa-Filho, Antonio José; Cilli, Eduardo Maffud [UNESP] (Public Library of Science (PLoS), 2013)
Antimicrobial peptides (AMPs) isolated from several organisms have been receiving much attention due to some specific features that allow them to interact with, bind to, and disrupt cell membranes. The aim of this paper was to study the interactions between a membrane mimetic and the cationic AMP Ctx(Ile21)-Ha as well as analogues containing the paramagnetic amino acid 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amino-4-carboxylic acid (TOAC) incorporated at residue positions n = 0, 2, and 13. Circular dichroism studies showed that the peptides, except for [TOAC13]Ctx(Ile21)-Ha, are unstructured in aqueous solution but acquire different amounts of α-helical secondary structure in the presence of trifluorethanol and lysophosphocholine micelles. Fluorescence experiments indicated that all peptides were able to interact with LPC micelles. In addition, Ctx(Ile21)-Ha and [TOAC13]Ctx(Ile21)-Ha peptides presented similar water accessibility for the Trp residue located near the N-terminal sequence. Electron spin resonance experiments showed two spectral components for [TOAC0]Ctx(Ile21)-Ha, which are most likely due to two membrane-bound peptide conformations. In contrast, TOAC2 and TOAC13 derivatives presented a single spectral component corresponding to a strong immobilization of the probe. Thus, our findings allowed the description of the peptide topology in the membrane mimetic, where the N-terminal region is in dynamic equilibrium between an ordered, membrane-bound conformation and a disordered, mobile conformation; position 2 is most likely situated in the lipid polar head group region, and residue 13 is fully inserted into the hydrophobic core of the membrane. © 2013 Vicente et al.
Keywords: 2,2,6,6 tetramethylpiperidine 1 oxyl 4 amino 4 carboxylic acid; carboxylic acid; ceratotoxin like peptide; cyclic AMP; polypeptide antibiotic agent; trypsin; unclassified drug; alpha helix; amino terminal sequence; antimicrobial activity; Anura; Bacillus subtilis; Candida albicans; carboxy terminal sequence; circular dichroism; controlled study; Cryptococcus neoformans; drug screening; drug synthesis; electron spin resonance; Escherichia coli; fluorescence analysis; fluorescence spectroscopy; human; human cell; hydrophobicity; Hypsiboas albopunctatus; membrane binding; micelle; molecular interaction; nonhuman; protein secondary structure; Pseudomonas aeruginosa; residue analysis; sequence analysis; spin labeling; Staphylococcus aureus; structure analysis